My life and that of Plato are the same” (Hua XIV, 198): Husserl, the origin, and the philosophical question - Inverso, Hernán Gabriel (2023)
This is a reflection about some methodological issues related to the kind of question we address to the past. I want to start from an idea stated by Fausto Fraisopi regarding the complexity of phenomena and their exceedance. He says: it would be an illusion to think of freeing oneself from the speculative task by saying that the idea of first philosophy is devoid of meaning, he says (p. 223). Following in these footsteps, we will characterise some approaches to the type of ancient philosophical question often associated with first philosophy. Then we will dwell on certain contributions that come from phenomenology and refer to the radical interrogation about history and meaning.